Relationship between the risk of intestinal mucosal Epstein–Barr virus and/or cytomegalovirus infection and peripheral blood NK cells numbers in patients with ulcerative colitis: a cross-sectional study in Chinese population - Tian, Ye; Dai, Jinghua; Yang, Yunfeng; Guo, Xiaofeng; Wang, Wei; Li, Fengxia; Wang, Juzi; Liu, Ruiyun (Frontiers in Microbiology, 2024)
ObjectiveThis study aimed to analyze the relationship between the risk of common opportunistic pathogens Epstein–Barr virus (EBV) and cytomegalovirus (CMV) infection in intestinal mucosal tissues of Ulcerative Colitis (UC) patients and the number of peripheral blood NK cells.MethodsUC patients admitted to a third-grade class-A hospital from January 2018 to December 2023 were selected as research population. Clinical data of the patients were collected from the electronic medical record system. Additionally, samples of intestinal mucosal tissues were obtained for real-time fluorescence quantitative PCR to detect and analyze the viral load of CMV and EBV. Blood samples were collected for lymphocyte subsets analysis. Multivariable logistic regression models analyses was used to determine the odds ratio (OR) and 95% confidence interval (95% CI) for the independent association between NK cells and EBV/CMV infections in UC. We further applied the restricted cubic spline analysis and smooth curve fitting to examine the non-linear relationship between them.Results378 UC patients were enrolled. Of these patients, there were 194 patients (51.32%) with EBV /CMV infection. In multivariable logistic regression analyses NK cells was independently associated with EBV and/or CMV infection after adjusted potential confounders (OR 8.24, 95% CI 3.75–18.13, p < 0.001). A nonlinear relationship was found between NK cells and EBV/CMV infections, which had a threshold around 10.169. The effect sizes and CIs below and above the threshold were 0.535 (0.413–0.692), p < 0.001 and 1.034 (0.904–1.183), p > 0.05, respectively.ConclusionThere was a non-linear relationship between NK cells and EBV/CMV infections. The risk for EBV/CMV infections was not increased with increasing NK cells in individuals with NK cells ≥ 10.169%, whereas the risk for EBV and/or CMV infection was increased with an decreasing NK cells in those with NK cells < 10.169%. The risk of EBV/CMV infections increases when NK cells were below a certain level.